The Social Times of Network Spaces: Sequence Analysis of Network Formation and Foreign Investment in Hungary, 1987-2001 - Старк, Дэвид; Ведреш, Балаш (Journal of Economic Sociology, 2010)
In order to build the model that reflects the process of network ties formation between the enterprises since they were created as well as the impact of the foreign investment on this network within the whole period of fast fundamental economic transformation we gathered the full data about the history of the ownership form changes of 1696 biggest Hungarian companies during 1987-2001. Combining methods of network analysis and dynamic analysis of the sequence of network positions we disclosed different ways of using network recourses that allow firms to come over the uncertainty, hide or restructurise actives get information and provide legitimacy. In this period the ownership nested in the network grew, gained stability and attracted more and more foreign capital. Strong network of the recombined ownership appeared to be stable and integrated the foreign investment inside themselves. Despite that multinational corporations destroyed the networks of joined enterprises with the help of their subsidiaries and daughter companies, we got the evidence that at the same time they built other stable strong networks. The results of our investigation allow us to assume that developing economies do not necessarily face the involuntary choice between global and local embedded networks.